Strategi Pemasaran Kopi Lokal: Peran Brand Experience, Gaya Hidup, dan Value for Money dalam Membentuk Perilaku Konsumen Mahasiswa Lampung (Pendekatan SEM-PLS) - As-Sadili, Abu Hasan; Tambunan, Varingan Prianando; Oktaviani, Anggita Dwi; Marbudi (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Coffee has transformed into a part of lifestyle and social identity among university students. This study aims to analyze the determinants of students’ coffee-purchasing decisions by focusing on the influence of Brand Experience, Trend-Based Lifestyle, and Value for Money. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the relationships among variables. Primary data were collected through questionnaires distributed to students in Lampung Province. The results indicate that collectively, the three variables significantly influence purchasing decisions. Among them, Brand Experience emerges as the most dominant driving factor, followed by Trend-Based Lifestyle. Meanwhile, Value for Money also contributes to purchasing power, although its effect is not as strong as the first two variables. The findings conclude that students’ decisions to purchase coffee are shaped by an integration of emotional like experiential appeal, social–trend pressure, and rational value considerations. The study’s implications highlight the importance of holistic marketing strategies for local coffee businesses, not only offering products but also creating strong brand experiences that align with young consumers’ lifestyles